Evaluation of Self-Medication Practice among Pharmacy Students in Jordan - Alsous, Mervat; Elayeh, Eman; Abdel Jalil, Mariam; Alhawmdeh, Ebtesam (Jordan Journal of Pharmaceutical Sciences, 2018)
Problem: To assess the practice of self-medication, among pharmacy students. Experimental approach: A cross-sectional study was conducted for a period of three months. A pre-validated questionnaire was distributed to pharmacy students at the University of Jordan. A total of 256 students participated in the study. Major Findings: The prevalence of self-medication among pharmacy students was 86.7%. The prevalence of students who obtained their medication from pharmacies was 56.6%, and about 30.5% reported using drugs without a medical referral 5 to 6 times last year. The majority of students (83.2%) read the leaflet about the drug before using it. The two major reasons for self-medication were to save time and perceived non-seriousness of illness. The presence of severe pain and worsening symptoms were the main reasons to seek medical help. Cough and cold preparations, antibiotics and vitamins were the drugs most frequently used in self-medication. Conclusion: Self-medication is highly prevalent among pharmacy students at the University of Jordan. Students were aware of some facts about self-medication, however more effort to educate pharmacy students to promote responsible self-medication use is needed. Potential interventions, including strict policies from health authorities, should be applied to prohibit the provision of medicines without a prescription.